Energy Poverty in Sub-Saharan Africa: Policy Implications for Vietnam - Tu Ngoc Bui (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Energy poverty—defined by inadequate access to reliable and affordable energy services—continues to pose a major barrier to economic development, agricultural productivity, and environmental sustainability in Sub-Saharan Africa (SSA). This study explores the complex interrelationship between energy poverty, environmental degradation, and agricultural productivity in SSA, with the aim of extracting policy insights relevant to Vietnam, a developing country facing similar rural energy access challenges. Drawing on a comprehensive literature review and empirical evidence from SSA, the study identifies that rural electrification significantly boosts agricultural productivity, while environmental degradation exerts a detrimental effect. The impact of renewable energy adoption is found to be context-dependent, with both enabling and constraining factors. Using qualitative synthesis and comparative case study analysis, the research contextualizes these findings within Vietnam’s rural development landscape. The results suggest that Vietnam can strengthen energy access and agricultural outcomes by expanding rural electrification programs, investing in decentralized renewable energy systems, and enforcing environmental regulations to prevent resource degradation. Policy recommendations include promoting public-private partnerships, supporting digital innovations for precision agriculture, and tailoring energy strategies to local socio-economic conditions. By leveraging lessons from SSA’s experiences, Vietnam can make strategic progress toward achieving energy equity and sustainable development in its rural sectors.